2018
DOI: 10.1098/rsob.170229
|View full text |Cite
|
Sign up to set email alerts
|

Seeding of proteins into amyloid structures by metabolite assemblies may clarify certain unexplained epidemiological associations

Abstract: The accumulation of various metabolites appears to be associated with diverse human diseases. However, the aetiological link between metabolic alteration and the observed diseases is still elusive. This includes the correlation between the abnormally high levels of homocysteine and quinolinic acid in Alzheimer's disease, as well as the accumulation of oncometabolites in malignant processes. Here, we suggest and discuss a possible mechanistic insight into metabolite accumulation in conditions such as neurodegen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 84 publications
(135 reference statements)
1
24
0
Order By: Relevance
“…It is possible that some fibril polymorphs require mixtures of different tau isoforms to efficiently propagate (25), although in our hands, seeding mixtures of K18ϩ and K19ϩ (3R and 4R tau) did not dramatically improve the fidelity of seeding. Or, as recently proposed, amyloid formation may be steered by cellular co-factors and/or metabolites (28). In support of this, brain-derived CTE fibrils apparently enclose a hydrophobic molecule that may be necessary for faithful replication during in vitro seeding (12).…”
Section: Inhibitors Block Seeding By Disease-associated Tau Fibrilsmentioning
confidence: 58%
“…It is possible that some fibril polymorphs require mixtures of different tau isoforms to efficiently propagate (25), although in our hands, seeding mixtures of K18ϩ and K19ϩ (3R and 4R tau) did not dramatically improve the fidelity of seeding. Or, as recently proposed, amyloid formation may be steered by cellular co-factors and/or metabolites (28). In support of this, brain-derived CTE fibrils apparently enclose a hydrophobic molecule that may be necessary for faithful replication during in vitro seeding (12).…”
Section: Inhibitors Block Seeding By Disease-associated Tau Fibrilsmentioning
confidence: 58%
“…348 It was suggested that the presence of metabolite seeds could have a triggering effect on the eruption of amyloid-associated neurodegenerative disorders. 349 Indeed, it was shown that quinolinic acid, a wellestablished early marker of PD, could seed the aggregation of aS into amyloid fibrils. 340 This may provide the missing link between the metabolite profile and the development of various degenerative processes and may clarify certain unexplained epidemiological associations.…”
Section: Metabolite Amyloidosismentioning
confidence: 99%
“…340 This may provide the missing link between the metabolite profile and the development of various degenerative processes and may clarify certain unexplained epidemiological associations. 349 All of the experiments in metabolite amyloids until 2019 have been performed in vitro or in cell culture. It was recently demonstrated that a yeast model of metabolite aggregation could be constructed.…”
Section: Metabolite Amyloidosismentioning
confidence: 99%
“…In this study, we aimed to test our recently presented hypothesis in which we propose that metabolite accumulation and supramolecular structure formation is a fundamental mechanism that may contribute to the initial steps inducing toxicity of amyloids and consequent neurodegeneration [53]. We postulate that these metabolite assemblies can serve as nuclei that crossseed protein aggregation, thereby accelerating formation of pathological deposits of aggregation-prone proteins such as tau, β-amyloid and α-synuclein.…”
Section: Introductionmentioning
confidence: 99%